An investigation into the effectiveness of corporal punishment as a way of achieving discipline in schools: a case of high schools in Sanyati District, Mashonaland west province - Kagweda, Karl- marx (Midlands State University, 2017)
The study sought to determine the effectiveness of corporal punishment as a way of achieving discipline in schools. Corporal punishment was illegalised but continues to be in use in secondary schools, and this pushed the need for the study. The study employed a descriptive research design. The population of the study included teachers, learners and heads in High schools in Sanyati District. A sample of nineteen teachers, eighty-five learners and three heads of schools was used in this study. The study made use of questionnaires, interviews and observations to access relevant data. The data was presented in tables, being analysed according to the research questions. The findings of the study revealed that majority of teachers, learners and heads suggest corporal punishment to be effective. Although its prevalence has been reduced and its noted negative implications, the majority justify the effectiveness of corporal punishment in fostering discipline. The most significant conclusion of the study was that corporal punishment is suggested as more effective when compared to alternatives in Sanyati District High schools. Last but not least, the study recommended that corporal punishment should continue in use basing on its conclusion as effective.